Creating special image effect by image decomposition and reconstruction - Sun, Jiexi (2014)
Special effect in digital photography is a broad term; in general, it refers to the effect applied to photos or film which is able to draw attention and create impact that are seemingly impossible in an analogue way. They are often used to enhance or modify reality to raise aesthetic merit and to convey information in a more effective and creative way than it would be possible with typical photography.